A New Search Algorithm Based on Muti-Octagon-Grid - Zhu Weixing; Chen Xianyong; Li Xincheng (2009 2nd International Congress on Image and Signal Processing, 2009)
To cope with the defects of the fast search algorithms based on the UESA (unimodal error surface assumption) that can easily lead to a local minimum or wrong search direction and on the analysis of the characteristics of many kinds of motion sequences, a new search algorithm based on the Muti-Octogon-Grid (MOGS) is proposed. The algorithm takes adaptive search strategies by using the distribution characteristics of motion vector and some other technologies, such as the adaptive threshold of macro-block and dynamic search range. Experimental results show that, compared with the UMHexagonS and Full Search, the algorithm maintains the same image quality and bit-rate, but it makes great improvement on the search speed and encoding time. The PSNR (Peak Signal-toNoise Ratio) increases about 0.004dB, the SIR (the Speed Improvement Rate) is 42% and 91%, the encoding time can be reduced by 21% and 78%, only with the bit-rate increased by 2.1% and 3.0% respectively on average.